2023
DOI: 10.3389/fphar.2022.971443
|View full text |Cite
|
Sign up to set email alerts
|

Piper sarmentosum Roxb. methanolic extract prevents stress-induced gastric ulcer by modulating oxidative stress and inflammation

Abstract: This study investigated the gastroprotective effect of Piper sarmentosum (PS) on stress-induced gastric ulcers in rats by measuring its effect on oxidative stress, gastric mucosal nitric oxide (NO), and inflammatory biomarkers. Twenty-eight male Wistar rats were randomly divided into four groups; two control groups (non-stress and stress) and two treated groups supplemented with either methanolic PS extract (500 mg/kg body weight) or omeprazole (OMZ; 20 mg/kg) orally. After 28 days of treatment, the stress con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On a group of test rats, Piper sarmentosum supplementation significantly reduced the results of gastric lesions and, interestingly, proved more effective than omeprazole. This study shows that oral Piper sarmentosum supplementation supports protection against the occurrence of gastric lesions, so it is a potential therapeutic agent for gastric ulcers [56]. Unfortunately, studies to date do not describe a direct effect of Piper sarmentosum on gastric cancer.…”
Section: Piper Sarmentosummentioning
confidence: 65%
“…On a group of test rats, Piper sarmentosum supplementation significantly reduced the results of gastric lesions and, interestingly, proved more effective than omeprazole. This study shows that oral Piper sarmentosum supplementation supports protection against the occurrence of gastric lesions, so it is a potential therapeutic agent for gastric ulcers [56]. Unfortunately, studies to date do not describe a direct effect of Piper sarmentosum on gastric cancer.…”
Section: Piper Sarmentosummentioning
confidence: 65%
“…Stress is a body response to harmful stimuli. It has been reported that stress-induced gastric ulceration is associated with mortality [ 42 , 43 ]. Restrain water immersion stress-induced gastric ulcer is a model widely used for investigating drugs that can be used to treat diseases related to stress [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Restrain water immersion stress-induced gastric ulcer is a model widely used for investigating drugs that can be used to treat diseases related to stress [ 44 , 45 ]. Stress-induced gastric ulcer is related to vagal overactivity, oxidative stress and free radical generation, and the decrease of gastric mucosal blood flow, resulting in gastric ulcer formation [ 42 , 46 , 47 ]. In the present study, TS significantly reduced gastric lesions in restraint water immersion stress-induced ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves and aerial parts of the plant have been particularly significant in these compound discoveries. Several pharmacological agents, including antiosteoporosis ( Suhana Mohd Ramli et al, 2012 ; Ekeuku et al, 2023 ; Zainol Abidin et al, 2023 ), anti-inflammatory agents ( Zakaria et al, 2010 ; Makchuchit et al, 2017 ; Akmal et al, 2022 ), antioxidants ( Ugusman et al, 2011 ; Wang et al, 2017 ), antimalarial agents ( Najib Nik A Rahman et al, 1999 ), antimicrobial agents ( Masuda et al, 1991 ), antihypertensive agents ( Mohd Zainudin et al, 2015 ; Othman et al, 2022 ), antidiabetic agents ( Othman et al, 2022 ; Nguyen et al, 2023 ), anticancer agents ( Zainal Ariffin et al, 2009 ; Hematpoor et al, 2018 ) and neuroprotective ( Ridtitid et al, 1998 ; Yeo et al, 2018 )agents, have been found.…”
Section: Introductionmentioning
confidence: 99%